An annotated checklist of the orchids of Western Himalaya, India - Jalal, Jeewan Singh; Jayanthi, J. (Lankesteriana: International Journal on Orchidology, 2015)
A checklist of the Orchidaceae of Western Himalaya is presented based on recent orchid explorations and herbarium collections. This checklist comprised of 239 taxa of orchids belonging to 72 genera. Of these, 130 are terrestrial, 13 mycoheterotrophic and 96 epiphytic. Thirteen (13) species are endemic to Western Himalaya. The best represented genus is Dendrobium, with 16 species followed by Habenaria with 14 species and Bulbophyllum with 12 species. In this checklist habit, habitat, phenology, elevational range of distribution etc. are provided.